The correlation between phase formation and the structure of the pellets with the fungal immobilization study as a commercial substrate culture/planting material - Rattiphorn SUMANG; Rampai KODSUEB; Narathip VITAYAKORN; Ruangwut CHUTIMA (My University, 2022)
Calcined clay pellets are popular planting material for those who love to grow plants in pots. The calcined clay pellets consist of clay (C), phosphate rock (PR), and rice husk ash (RHA). [(1-x)(50C–50PR)-xRHA], x(RHA) = 0, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, and 0.65 wt% were prepared by a conventional solid-state reaction method. The samples were made into a spherical shape with a diameter of 10 mm and fired at 600℃ to 1000℃. The effect of x contents on phase formation, microstructure, and chemical properties of [(1-x)(50C–50PR)-xRHA] was studied. X-ray diffraction revealed the typical assemblages with quartz, illite, and kaolinite in all the samples. SEM images of samples showed irregular packing and a highly porous microstructure. The addition of x(RHA) contents results in porous microstructure in all the samples. The surface area and pore volume of samples increased from 8.83 m2·g-1 to 14.71 m2·g-1 and 0.938 cm3·g-1 to 0.942 cm3·g-1, respectively, with the increase of x(RHA). The density of the samples slightly decreased from 2.45±0.06 g·cm-3 to 1.94±0.05 g·cm-3, with an increase in x(RHA) contents. The capability of calcined clay pellets to immobilize plant growth-promoting fungi was then studied. The results showed that orchid endophytes, as plant growth-promoting fungi, grow well on the calcined clay pellets saturated with potato dextrose broth (PDB). Besides, all fungi can live on calcined clay pellets and stay viable for at least 35 days after inoculation. These results suggested that the calcined clay pellets could serve as planting material that enhances plant growth (via its nutrients and growth-promoting fungi) simultaneously.
Keywords: Husk; Plant Pathogens and Fungal Diseases